Comparative evaluation of management of gingival recession using subepithelial connective tissue graft and collagen membrane by periodontal microsurgical technique: A clinical study of 40 cases - Prasanth Thankkappan; Subrata Roy; Vivek Bapurao Mandlik (Wolters Kluwer Medknow Publications, 2016)
Background: New technologies, instruments, and surgical techniques are necessary to help the clinician ensure the best result and satisfy the patient's expectations, and surgical microscope has been thoroughly demonstrated as a useful tool. A clinical study was carried out to compare 2 different types of root coverage procedures using periodontal microsurgical procedure. Materials and Methods: Forty patients were selected and divided into Group A and Group B. Group A subjects were treated with subepithelial connective tissue graft (CTG) whereas Group B subjects were treated using a resorbable collagen membrane. The procedures were performed with the help of an operating microscope using 250 mm objective lens and ×6 magnification. Results: A comparison between baseline, 1, 3, and 12 months have been done between groups among all parameters. It has been noticed that the root coverage was better in Group A subjects at all time. At 12 months, Group A showed 81.42% coverage where in Group B it was 70.08%. Similarly, increase in the width of keratinized gingiva and attached gingiva were more in Group A. Conclusions: The present study showed that use of microsurgical instrument helped to deliver precise incision, better visual acuity, and improved illumination which facilitate to gain a better final outcome. Root coverage was better in the patients using CTG.